The scrotum narrates the inside story... - Prabudh Goel; Minu Bajpai; Jagjit Dalal (Wolters Kluwer Medknow Publications, 2021)
Pyoscrotum is rarely encountered in neonates and is secondary to a local pathology such as neglected torsion or epididymo-orchitis. Pyoscrotum from an intra-abdominal pathology is possible in the presence of a patent processus vaginalis and has been rarely reported in the context of acute appendicitis. We report our experience with a case of antenatal bowel perforation presenting postnatally after an absolutely asymptomatic "honeymoon" period.